2003
DOI: 10.1073/pnas.0436564100
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-dependent human transcriptome variability: Implications for chronic heart failure

Abstract: Heart failure (HF) is the end result of progressive and diverse biological adaptations within the diseased myocardium. We used cDNA microarrays and quantitative PCR to examine the transcriptomes of 38 left ventricles from failing and nonfailing human myocardium. After identification of a pool of putative HF-responsive candidate genes by microarrays on seven nonfailing and eight failing hearts, we used quantitative PCR and a general linear statistical model in a larger sample set (n ‫؍‬ 34) to validate and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 22 publications
1
77
1
Order By: Relevance
“…Human ventricular myocardial samples were obtained from 18 male patients with severe heart failure secondary to idiopathic dilated cardiomyopathy or ischemic heart disease and from 18 unused male donor hearts (25,28). The average ages of the two groups were 50.2 Ϯ 16.0 and 53.8 Ϯ 19.1 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human ventricular myocardial samples were obtained from 18 male patients with severe heart failure secondary to idiopathic dilated cardiomyopathy or ischemic heart disease and from 18 unused male donor hearts (25,28). The average ages of the two groups were 50.2 Ϯ 16.0 and 53.8 Ϯ 19.1 years.…”
Section: Methodsmentioning
confidence: 99%
“…Real Time PCR, Western Blotting, and ELISA-Total RNA was reverse-transcribed, and PCRs were run in the presence of SYBR green (28 Adenovirus and Adenoviral Infection-A recombinant replication-defective adenovirus encoding a hemagglutinin (HA) epitope-tagged constitutively activated AKT-1 and a control virus expressing no gene product (Ad/CMV/DEST-null) were constructed by recombination cloning from a plasmid encoding myr-AKT1-HA (gift of T. Francke, Columbia University) into pAd/CMV/V5-DEST vector (Invitrogen) to generate pAd/CMV/DEST-myrAkt1-HA. The viruses were commercially amplified, purified, and titered (Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…85 In the study by Boheler et al, 85 11 genes in failing hearts vary by sex, including calponin 1, insulin growth factor-binding protein 4, mitogen-activated protein 4 kinase 5, and cyclin-dependent kinase inhibitor. The directional change in gene expression depends on sex.…”
Section: Gene Expression Arraymentioning
confidence: 99%
“…It is equally conceivable that molecular differences exist between sexes in the LV remodeling process. 44,45 Investigators have reported sexrelated differences in remodeling at the cardiomyocyte level, influenced partly by MMP activation. 46 In the early phase of volume overload, male animals have smaller myocyte lengths as the result of amitotic division of binucleate cardiomyocytes, whereas female animals have increased length of myocytes.…”
Section: Sex Differences In Relations Of Detectable Plasma Mmp-9 To Lmentioning
confidence: 99%